Poverty and Intersectionality: A Multidimensional Look into the Lives of the Impoverished. (June 2014) - Saatcioglu, Bige; Corus, Canan
Subsistence consumers are disadvantaged and marginalized on many levels, including financial deprivation, poor health, lack of access to resources, and social stigmatization. The disadvantages experienced by subsistence consumers are interconnected and co-constitutive; being disadvantaged in one domain often intersects with other disadvantages, contributing to an overall vulnerability within the market system. Drawing from the intersectionality paradigm, the authors examine an overlooked low-income community that shares elements of subsistence contexts. The findings reveal multiple ways in which a trailer park community residents experience and manage intertwined disadvantages. Several overlapping identity categories (i.e., socio-economic status, health status, and type of housing) vis-à-vis structural and relational dynamics are fleshed out. Implications for research on subsistence marketplaces and the usefulness of the intersectionality approach for macromarketing research are discussed.